Longitudinal and Comparative Perspectives on the Competitiveness of Countries: Learning from Technology and the Telecom Sector - Mittal, Sudhir; Momaya, Kirankumar; Agrawal, Sushil (Pontificia Universidad Católica del Perú. CENTRUM, 2013)
Country competitiveness is gaining importance across the world in the face of complex economic challenges. There is a need to revisit factors of competitiveness and evolve better evaluation methods. The linkage between technological and overall country competitiveness has not been sufficiently explored, particularly in the context of emerging countries. India is one of the leading large emerging countries, and it is trying to improve its overall competitiveness and growth through technology. The purpose of this paper is to present better criteria and indices of overall and technological competitiveness and to develop comparative views of the major countries. The data are compiled from best of competitiveness reports and other sources. Composite indices were developed to promote comparative perspectives. While emerging countries like Brazil, China, and Russia, which share similarities with India, have duly recognized the importance of innovation, technology development, and research and development, India needs to perform a major catch-up on technological competitiveness to sustain its long-term overall competitiveness. The emerging scenarios have rich insights and implications for discerning leadership in industry, governments, and academia. The paper provides longitudinal perspectives and rich, comparative, insightful views for leaders to plan actions to enhance technological and overall competitiveness.
Keywords: Country competitiveness; Emerging countries; Technological competitiveness; Technology management; Telecom sector; https://purl.org/pe-repo/ocde/ford#5.02.04